Rethinking chemistry in higher education towards technology-enhanced problem-based learning. Issue 2 (1st January 2016) - Ramstedt, Madeleine; Hedlund, Tomas; Björn, Erik; Fick, Jerker; Jahnke, Isa
Abstract : A range of factors can lead to situations where university courses have to be taught with a very small number of students. In this paper, we report on our experiences of a chemistry course that was especially designed to encourage learning in small groups of students (four to five per course). The course design included inquiry-based approaches, case methodology and problem-based learning concepts. The main goal was to enhance student motivation and to support them to become active agents ('pro-sumers'). Technology was adopted to support students in their inquiry-based learning processes by using online logs, group wikis and quizzes and with sections of laboratory work. We explored student perceptions during the first 2 years in two courses. The students were, in general, very positive about the course and communicated that the technological tools along with the pedagogical design decisions had assisted them to different extents in their learning. Our conclusion is that such a design is appropriate for an advanced-level chemistry course with small numbers of students, and the course will continue to be given in this form.